FAIR‐compliant clinical, radiomics and DICOM metadata of RIDER, interobserver, Lung1 and head‐Neck1 TCIA collections. Issue 12 (1st March 2021) - Kalendralis, Petros; Shi, Zhenwei; Traverso, Alberto; Choudhury, Ananya; Sloep, Matthijs; Zhovannik, Ivan; Starmans, Martijn P.A.; Grittner, Detlef; Feltens, Peter; Monshouwer, Rene; Klein, Stefan; Fijten, Rianne; et al.
Abstract : Published in Medical Physics, Vol. 47, No. 11